DECONSTRUCTING THE SOCIAL ORDER AS A REFLECTION OF THE PLAY-AGE PERSONALITY IN THE POEM “GOD HAD DIED” BY SUBAGIO SASTROWARDOJO - Prautomo, Adi; Wahyuni (Prologue: Journal on Language and Literature, 2026)
The purpose of this research is to deconstruct the psyche in a playing time that is started from creating a desire to know many new things by studying them and to master them by experimenting with planning, persuasion, expanding mastery and trying to restore to their original form with a sense of responsibility to achieve tasks and goals. The literary psychology approach is used in this research because psychoanalysis is one term used to research human psychology using the  psychosocial theory from Erik.H.Erikson. Erikson formulates his concept of the development of the circle of human life through eight (8) stages from infant to elderly. In analyzing the data, researcher uses the poem God Had Died as an analysis material. Data analysis uses literal meanings and figurative meanings. The metaphorical meaning uses the figurative language in the form of personification and metaphor. The results of the research, the researcher finds the character does not recognize the being of God, there is disharmony or harmony has been dirty, the leader does not have leadership qualities, all betrayed and deceptive, drifts into a pleasure, and finally dirty things are pleasures.